Exploring The Benefits of Social Media Video Platforms for Learning Speaking Skills at SMP 34 Medan: Penelitian - Khairunnisa Harahap; Wariyati; Irpan Apandi Batubara; Rini Fadhillah Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to explore how the benefits of social media platforms such as Youtube ,Instagram ,and Tiktok to help junior high school students learn their English speaking skils .The method used in this study is a qualitative approach through semi-structured interviews with 10 students from high school level. The respondets were selected purposively by considering their experience in using social media as a means of learning English, especially speaking skilss. The results show that Youtube helps students imitate the pronunciation of native speakers, Instagram helps add new vocabulary, and Tiktok makes students more confident in speaking through short videos. All of these of these platforms make students more enthusiastic about learning and practicing speaking English in a fun way.